Meeting the challenges of clinical information provision. (12th May 2011) - Spring, Hannah
Abstract: This virtual issue of the Health Information and Libraries Journal ( HILJ ) has been compiled to mark the 5th International Clinical Librarian Conference 2011 . In considering the challenges of clinical information provision, the content selected for the virtual issue offers an international flavour of clinical information provision and covers a variety of different facets of clinical librarianship. The issue broadly covers the areas of information needs and preferences, clinical librarian roles and services, and education and training, and reflects the way in which a normal issue of the HILJ would be presented. This includes a review article, a collection of original articles, and the three regular features which comprise International Perspectives and Initiatives, Learning and Teaching in Action, and Using Evidence in Practice . All papers included in this virtual issue are available free online.